PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV C SDN 024 TARAI BANGUN KECAMATAN TAMBANG - Selvi Erizal; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research is held because of a low students' learning result of IPS subject of students of class IV C SDN 024 Tarai Bangun. From 42 students, there are 33 students that achieve the KKM (21,42%). There are 33 students that did not achieve the KKM yet (78,57%) with the average of 50,59. The purpose of this research is to increase the learning result of IPS subject of students of class IV C SDN 024 Tarai Bangun with the implementation of The power of two learning model. The analysis of research result, the basic score of students' learning result of IPS subject, has increased in cycle I and II from 50,59 increased by 31,43% become 82,02 And increased again by 3,69% become 85,71. The completeness of students learning result of IPS subject also increased from students'basic score 21,42% (not complete) increased by 83.33% (complete) in cycle I and in cycle II and increased again by 95,23% (complete). The percentage of teacher's activity after the implementation of The power of two learning model in the first meeting by 75% with good category. In the second meeting of first cycle, the percentage increased become 83,22% with good category. In the first meeting of cycle II the percentage of teacher's activity has increased again become 91,66% with very good category, in the second meeting of cycle II the percentage of teacher's activity has increased again become 95,83% with very good categoty. The percentage of students' activity in the first meeting 75% with good category, in the second meeting of cycle I the percentage of students activity has increased again become 79,16% with good category, in the first meeting of cycle II the percentage of students activity has increased again become 87,5% eith good category, in the second meeting of cycle II the percentage of students' activity has increased again become 91,66% with very good category. We can conclude that the implementation of the power of two type of cooperative learning can increase the student's learning result of IPS subject of students of class IV C SDN 024 Tarai Bangun.Key words: The power of two, IPS subject learning result